Surrounded : America's first school for Black girls, 1832 - Lupano, Wilfrid, 1971- (NBM Graphic Novels, 2025)
In 1832, in Canterbury, Connecticut, a "charming and picturesque" little school for young girls opens to accommodate around twenty residents. Educating girls is a bit ridiculous and useless, they think in the area, but harmless enough. Until the day, when the "charming school" led by Prudence Crandall, announces that it will now welcome Black girls... Thirty years before the abolition of slavery, some fifteen young people in the Crandall school are greeted by a wave of hostility of insane proportion. White America is afraid of some of its children. The story of this school and its legal legacy for civil rights cannot be understated. Crandall v. State (of Connecticut) was the first full-throated civil rights case in U.S. history. The arguments by attorneys in the Crandall case played a role in two of the most fateful Supreme Court decisions, Dred Scott v. Sandford, and the landmark case of Brown v. Board of Education. It catapulted Ms. Crandall into a Civil Rights pioneer.